Measurement properties of the Minimal Insomnia Symptom Scale (MISS) among cardiac arrest survivors – A Rasch evaluation study - Patrik Hellström; Johan Israelsson; Erik Blennow Nordström; Carina Hjelm; Anders Broström; Peter Hagell; Kristofer Årestedt (Resuscitation Plus)
Introduction: Cardiac arrest (CA) survivors often face significant health challenges, including insomnia, which can adversely affect their health-related quality of life. The Minimal Insomnia Symptom Scale (MISS) is a brief, self-reported instrument designed to screen for insomnia. This study aimed to identify the measurement properties of the MISS in CA survivors and to explore a relevant cut-off score. Methods: Data were collected from two studies: a health survey of CA survivors and a sub-study of a randomized controlled trial (RCT) on targeted temperature management (TTM2). A total of 269 CA survivors participated, with 212 from the survey and 57 from the RCT, the data was collected 6–7 months after CA. The MISS was evaluated using the polytomous Rasch model, focusing on model fit, local independence, response category functioning, targeting, reliability, and differential item functioning (DIF). Results: In total, 212 participants were males and 57 females, with a mean age of 66 years. Overall, 51% had survived in-hospital CA and 49% out-of-hospital CA. The MISS exhibited acceptable model fit and targeting, with no disordered thresholds or DIF for age, sex, or place of arrest. The reliability was acceptable. The suggested optimal cut-off score for identifying insomnia was ≥6 points. Conclusions: The findings indicate that MISS is a valid and reliable screening instrument for insomnia in CA survivors. These results support the use of MISS for screening insomnia in CA survivors.